Psychological Processes and Institutional Actors in the Sustainable Energy Transition: A Case-Study Analysis of a Local Community in Italy - Tiberio, Lorenza; De Gregorio, Eugenio; Biresselioglu, Mehmet Efe; Demir, Muhittin Hakan; Panno, Angelo; Carrus, Giuseppe (Frontiers in Psychology, 2020)
This paper presents the results of a qualitative study exploring the role of formal social units in the sustainable energy transition process. A small community in North-east Italy was assumed as case study, in the context of a wider EU-funded research project aimed at understanding the individual and collective dimensions of energy-related choices. Starting from a general framework and integrated approach to explain sustainable energy transitions proposed by Steg et al. (2015), the main aim of our study was to identify the psychological and social factors that motivated the key actors to undertake an energy self-sufficiency path in the case-study area. Our analyses aimed at understanding the social, cultural, and socioeconomic dynamics in the energy transition process of the community. The study outlined how these factors contributed to foster collaborative actions between public decision makers, relevant stakeholders, civil society and citizens. Results of a computer-supported qualitative content analysis using the software MAXQDA helped to shed light on the specific mechanisms and dynamics driving energy choices and energy-related behaviour among the community. The implication for best practices and successful implementations of energy transition process in small communities emerging from this case study are discussed.